2002
DOI: 10.1256/qj.00.35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flow through the Canadian Archipelago and Bering Strait on the North Atlantic and Arctic circulation: An ocean modelling study

Abstract: SUMMARYAn ocean general-circulation model with an orthogonal curvilinear grid is presented, with the grid north pole over Greenland to achieve improved resolution in the Greenland and Labrador Seas. The model is integrated for 4500 years in ve different experiments, with open and closed connections to the Arctic via the Bering Strait (BS) and Canadian Archipelago (CA). When the BS and CA connections are open the Atlantic overturning circulation has a realistic strength (20 Sv), whereas there is stronger overtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 66 publications
4
76
1
Order By: Relevance
“…In both simulations the Arctic liquid FW content increases rapidly during the first 20-30 years, the same as in other ocean 25 climate models participating in the CORE-II intercomparison project analyzed by Wang et al (2016b). They showed that the source of excessive FW is sea surface salinity (SSS) restoring.…”
Section: Freshwatersupporting
confidence: 69%
See 1 more Smart Citation
“…In both simulations the Arctic liquid FW content increases rapidly during the first 20-30 years, the same as in other ocean 25 climate models participating in the CORE-II intercomparison project analyzed by Wang et al (2016b). They showed that the source of excessive FW is sea surface salinity (SSS) restoring.…”
Section: Freshwatersupporting
confidence: 69%
“…After initial spin-up the depth of temperature maxima is located at about 400 m in LOW, while in HIGH it remains at about 300 m, the observed depth suggested by the hydrographic climatology. In the Canadian Basin the thickening and deepening of the AW layer is also 25 very obvious in LOW. In this simulation the core of the AW layer deepens by about 100 m, changing from about 450 m to 550 m during the 60 model years.…”
Section: Spin-up Of the Aw In Arctic Basinsmentioning
confidence: 99%
“…In coarser-resolution models the complex network of islands and channels in this region are poorly represented (if at all). However, having an accurate representation of these straits has been shown to play an important role in obtaining a realistic strength for the MOC in a climate model, as it controls the fraction of freshwater exported either directly into the Nordic or Labrador Seas where it plays a role in modulating deep convective overturning (Wadley and Bigg 2002). Our finding that the flow through the Canadian Archipelago remained high as the model began to equilibrate after 30 yr of NAO1 forcing reiterates the need to resolve this region in order to accurately model the transport of freshwater from the Arctic to the sub-Arctic seas.…”
Section: Discussionmentioning
confidence: 99%
“…This inflow is balanced by an outflow at the southern boundary of the domain in the Atlantic Ocean. Although the seasonal variability of the Bering Strait transport is not considered, it seems to have a rather limited impact on the circulation (Ness et al, 2010;Wadley and Bigg, 2002).…”
Section: The Modelmentioning
confidence: 99%